Remote data logger with multi-sensor for greenhouse - Lam, Kheng Yik (2012)
A data logger or a data acquisition system is an electronic device common in measurement application. The basic form of data logger is to capture and store the environment parameters over a period of time with incorporating sensors. This stand alone device measure, collect and store data on the Secure Digital (SD) card. Microcontroller is used in this system to perform the job. The system is equipped with several sensors such as temperature, humidity, lights intensity and air contaminants. The data can be analyzed in standard condition or using Personal Computer (PC) for offline analysis and report. In the end, microcontroller Atmega32 system board is able to display four parameters from each sensor on Liquid Crystal Display (LCD).